Evaluation of two lanthanide complexes for qualitative and quantitative analysis of target proteins via partial least squares analysis - Goicoechea, Hector Casimiro (2005)
Two lanthanide complexes, namely 5-aminosalicylic acid ethylenediaminetetraacetate europium(III) (5As-EDTA-Eu3+) and 4-aminosalicylic acid ethylenediaminetetraacetate terbium(III), were evaluated for the analysis of carbonic anhydrase, human serum albumin (HSA), and c-globulin. Quantitative analysis is based on their luminescence enhancement upon protein binding and qualitativeanalysis on their lifetime capability to recognize the binding protein. Analytical figures of merit are presented for the three proteins. The limits of detection with 5As-EDTA-Eu3+ are at the parts per billion level. Partial least square regression analysis is used to determine HSA and c-globulin in binary mixtures without previous separation at the concentration ranges typically found in clinical tests of human blood serum.